EKSPLOITASI KAPITALISME TERHADAP PEREMPUAN; : Sebuah Kritik Ideologi - Akmal Saputra (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This article is actually criticizing the regime of capitalism that has exploited Indonesian women. Today's capitalism is a manifestation of globalization called advanced or postmodern capitalism, globalization has had a tremendous impact on the lives of Indonesians in the social, economic, political, cultural, health and religious fields, both positive and negative. In this artkkel the author also describes the impact of globalization and criticizing the regime of capitalism that exploits women, in other words women